Contruction of Criminal Law Against Blaspheming the President as the Head of Government in Indonesia - Holijah, Holijah; Rizal, M. (Nurani, 2023)
The State of Indonesia is a state of law, every citizen gets protection of both civil and political rights. In addition, as a country that adheres to a presidential system of government, the position of the President is both head of state and head of government. However, there is an update efforts to provide better protection for the dignity of the President in the Criminal Law raises pros and cons, of course it is very interesting to study more deeply, namely regarding the norm of defamation against the president and the limits to the concept of norms of defamation against the president for the protection of dignity as head government. The research method used in this paper is through normative juridical research using primary data sources derived from secondary data. Secondary data from primary, secondary and tertiary legal materials that are directly related to the problems written. The conclusions in the research show that the legal norms and concepts regarding insulting the president in the the 2019 Draft Criminal Law (RUUKUHP) are in an effort to maintain the existence of the president as a person because everyone has legal rights to protect human dignity and worth. Furthermore, the concept of protecting the dignity of the president or vice president in the article does not mean protecting government policies from criticism.